Effect of investor sentiment on the price movements of cryptocurrency - Go, Christopher Tan (Animo Repository, 2022)
Cryptocurrency is a digital asset that is designed to be a medium of exchange. It is not generally issued by a central authority which renders cryptocurrency virtually immune to government intervention. Cryptocurrency trading is typically associated with the high volatility that comes with the market. Thus, in recent years, several discussions were made in order to assess which variables are likely causing the market’s high volatility. This study aims to investigate whether investor sentiments will have an impact on the returns and volatility of two of the major cryptocurrencies in the market. Investor sentiments are integrated into the GARCH model in order to assess whether these sentiments are useful in estimating volatility. The study’s findings suggest that investor sentiments have a positive effect on bitcoins returns. In addition, it has been found that negative news and sentiments affect bitcoin’s volatility greater than positive sentiments of a similar magnitude. The study has not found any significant relationship between investor sentiments and ethereum returns and volatility.